Discovery of N-(2-Aminophenyl)-4-(bis(2-chloroethyl)amino)Benzamide as a Potent Histone Deacetylase Inhibitor - Lihui Zhang; Xiaoyang Li; Yiming Chen; Minghui Wan; Qixiao Jiang; Li Zhang; C. James Chou; Weiguo Song; Lei Zhang (Frontiers Media S.A., 2019)
Inhibition of histone deacetylases (HDACs) has been an important emerging therapy for the treatment of multiple cancers. However, the application of HDAC inhibitors is restricted by the limited potency against solid tumors. In order to discover novel HDAC inhibitors with potent antitumor activities, nitrogen mustard group was introduced to the structure of CI994. The derived molecule N-(2-aminophenyl)-4-(bis(2-chloroethyl)amino)benzamide (NA) exhibited enzyme inhibitory pattern of class I selectivity with IC50 values of 95.2, 260.7, and 255.7 nM against HDAC1, HDAC2, and HDAC3, respectively. In the antiproliferative assay, NA exhibited 10.3-fold (2.66 μM) and 11.3-fold (1.73 μM) higher potency than did suberoylanilide hydroxamic acid (SAHA) (27.3 and 19.5 μM) in inhibition of A2780 and HepG2 cell growth, respectively. Further HepG2 cell-based cell cycle and apoptosis studies revealed that induction of the G2/M phase arrest and cell apoptosis contributes to the antitumor effects of NA. It is suggested that NA could be utilized as a lead compound in the development of bifunctional HDAC inhibitors for the treatment of solid tumors.